Identification of Mycobacterium species and Rhodococcus equi in peccary lymph nodes - de Morais, Amanda Bonalume Cordeiro [UNESP]; Bolaños, Carmen Alicia Daza [UNESP]; Alves, Ana Carolina [UNESP]; Ikuta, Cássia Yumi; Lara, Gustavo Henrique Batista [UNESP]; Heinemann, Marcos Bryan; Giuffrida, Rogério; Listoni, Fernando Paganini [UNESP]; de Souza Ribeiro Mioni, Mateus [UNESP]; Motta, Rodrigo Garcia; Takai, Shinji; Ribeiro, Márcio Garcia [UNESP] (Springer Nature, 2018)
Mycobacterium species and the virulence-associated proteins (vapA, vapB, and vapN genes) of Rhodococcus equi isolated from 330 lymph nodes of collared peccaries (Tayassu tajacu) and white-lipped peccaries (Tayassu pecari) intended for human consumption were investigated. Thirty-six (10.9%) R. equi strains were isolated; 3.3% (n = 11/330) were from white-lipped peccary lymph nodes, and 7.6% (25/330) were from collared peccary lymph nodes. Among the 11 isolates of R. equi from the white-lipped peccaries, 90.9% (n = 10/11) were obtained from the mesenteric lymph nodes, and only 9.1% (n = 1/10) were obtained from the mediastinal lymph nodes. In the 25 isolates of R. equi obtained from the collared peccaries, 40.0% (n = 10/25) were recovered from the mesenteric lymph nodes, 36% (n = 9/25) from the submandibular lymph nodes, and 24.0% (n = 6/25) from the mediastinal lymph nodes. No vapA, vapB, or vapN genes (plasmidless) or three host-associated types (pVAPA, pVAPB, and pVAPN) were identified among the R. equi isolates. Mycobacterium species were isolated in 3.03% (n = 10/330) of all the lymph nodes analyzed. Among the 10 mycobacterial isolates, 60% (n = 6/10) were from the white-lipped peccary lymph nodes, and 40% (n = 4/10) were from the collared peccary lymph nodes. Ten Mycobacterium species were detected by PCR-PRA with a predominance of M. avium type 1. Sequencing of the hsp65 and rpob genes revealed mycobacteria that were saprophytic (M. sinense and M. kumamotonense) and potentially pathogenic (M. colombiense and M. intracellulare) to humans and animals. To our knowledge, this is the first description of R. equi and/or mycobacterial species identified in the lymph nodes of peccary specimens. R. equi (plasmidless) and the mycobacterial species described here have been reported as causes of pulmonary and extrapulmonary infections in both immunocompetent and immunocompromised humans.
Keywords: Collared peccary; Mycobacteria; Rhodococcosis; Tayassuidae species; White-lipped peccary